Pentecostalism in Africa : presence and impact of pneumatic Christianity in postcolonial societies - Lindhardt, Martin, (Global Pentecostal and Charismatic Studies, 2014)
Within recent decades Pentecostal/charismatic Christianity has moved from an initially peripheral position to become a force to be reckoned with within Africa's religious landscape. Bringing together prominent Africanist scholars from a wide range of disciplines, this book offers a comprehensive and multifaceted treatment of the ways in which Pentecostal-Charismatic movements have shaped the orientations of African Christianity and extended their influence into other spheres of post-colonial societies such as politics, developmental work and popular entertainment. Among other things, the chapters of the book show how Pentecostal/charismatic Christianity responds to social and cultural concerns of Africans, and how its growth and increasingly assertive presence in public life have facilitated new kinds of social positioning and claims to political power.